2020
DOI: 10.1021/acsmacrolett.0c00339
|View full text |Cite
|
Sign up to set email alerts
|

Compatibilization of iPP/HDPE Blends with PE-g-iPP Graft Copolymers

Abstract: The compatibilization of polyethylene (PE) and isotactic polypropylene (iPP) blends is of particular interest due to the challenges associated with recycling these plastics from mixed waste streams. Polyethylene-graft-iPP copolymers (PE-g-iPP) were prepared using a grafting-through strategy by copolymerization of ethylene with allyl-terminated iPP macromonomers in the presence of a hafnium pyridylamido catalyst. Graft copolymers with a variety of graft lengths (M n = 6–28 kg/mol), graft numbers, and graft spac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(83 citation statements)
references
References 22 publications
4
79
0
Order By: Relevance
“…119 Coates, Bates, LaPointe, and co-workers used differing bespoke PE/iPP multiblock copolymer topologies to lower compatibilizer levels while still dramatically toughening otherwise brittle blends. 120,121 Analogous work has been carried out by Loṕez-Barroń's group at ExxonMobil with similar results. 122,123 While these materials perform well, there are concerns that these complex blends will further complicate recycling efforts.…”
Section: ■ Sustainable Polymerssupporting
confidence: 61%
“…119 Coates, Bates, LaPointe, and co-workers used differing bespoke PE/iPP multiblock copolymer topologies to lower compatibilizer levels while still dramatically toughening otherwise brittle blends. 120,121 Analogous work has been carried out by Loṕez-Barroń's group at ExxonMobil with similar results. 122,123 While these materials perform well, there are concerns that these complex blends will further complicate recycling efforts.…”
Section: ■ Sustainable Polymerssupporting
confidence: 61%
“…[ 92,151,152 ] More recently, this research group has presented polyethylene grafted with isotactic polypropylene copolymers (PE‐ g ‐iPP) as blending agents for PP and PE with similar compatibilising effects as multi‐block copolymers. [ 153 ] The grafted compatibilisers are formed by copolymerising macromonomers in the presence of a hafnium pyridylamido catalyst rather than by living polymerisation. These new copolymer compatibilisers Thus, providing an economically favourable method to compatibilised MPO wastes.…”
Section: Mechanical Recycling Of Polyolefinsmentioning
confidence: 99%
“…These new copolymer compatibilisers Thus, providing an economically favourable method to compatibilised MPO wastes. [ 153 ] Successful compatibilization of polyolefins is of great interest to the recycling industry. The qualities of one polyolefin can be used to enhance that of another.…”
Section: Mechanical Recycling Of Polyolefinsmentioning
confidence: 99%
“… 28 More recent studies investigating MBCP compatibilizers with four or more blocks—enabled by synthetic advancements—have revealed that MBCPs actually outperform traditional diblocks. 18 , 35 37 These and other recent advances are discussed in depth in later sections of this perspective.…”
Section: Introductionmentioning
confidence: 97%